The Role of Mobile Decoder Flashcards for Students' Learning Outcomes, Islamic Values, and Learning Motivation - Marzuq, Achmad Barik; Fajaroh, Fauziatul; Budiasih, Endang; Muntholib, Muntholib (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
Students, especially Muslims, are encouraged to consume halal and healthy food and tayyib (lawful). However, students faced a problem with how to distinguish good food. The current study aimed to investigate the benefits of using Problem-based learning (PBL) integrated with Islamic values with a decoder as learning media in increasing learning outcomes, Islamic value, and learning motivation for chemistry subjects this paper aims to examine the predictive role of mobile DECODER flash card for learning outcomes, Islamic values and learning motivation on high school students. The research was conducted on a representative sample (N = 120) of students in Pasuruan, East Java, Indonesia. Mobile Decoder Flashcards affect Islamic Values and the learning motivation of students. Students with higher Islamic Values are more interested and pay more attention during learning activities. The results of this research confirm that the Mobile DECODER Flashcard positively affects students' Islamic values and learning motivation. This study's findings show a higher score for experimental class students' Islamic values and learning motivation than the control class students' scores.